History of the Development of Philosophy in A Social and Ideal Context - Sh. F, Djurayev. (Journal of Innovation in Education and Social Research, 2025)
The article briefly highlights the main stages of the development of philosophy in the context of the development of society. From ancient times to the present day, philosophy has been a social indicator of changes in the development of society. Philosophy not only reflected changes in society but also actively influenced the worldview of people in this society.